The state of the science of nurse work environments in the United States: A systematic review - Holly Wei; Kerry A. Sewell; Gina Woody; Mary Ann Rose (Elsevier, 2018)
A healthy nurse work environment is a workplace that is safe, empowering, and satisfying. Many research studies were conducted on nurse work environments in the last decade; however, it lacks an overview of these research studies. The purpose of this review is to identify, evaluate, and summarize the major foci of studies about nurse work environments in the United States published between January 2005 and December 2017 and provide strategies to improve nurse work environments. Databases searched included MEDLINE via PubMed, CINAHL, PsycINFO, Nursing and Allied Health, and the Cochrane Library. The literature search followed the PRISMA guideline. Fifty-four articles were reviewed. Five major themes emerged: 1) Impacts of healthy work environments on nurses' outcomes such as psychological health, emotional strains, job satisfaction, and retention; 2) Associations between healthy work environments and nurse interpersonal relationships at workplaces, job performance, and productivity; 3) Effects of healthy work environments on patient care quality; 4) Influences of healthy work environments on hospital accidental safety; and 5) Relationships between nurse leadership and healthy work environments. This review shows that nurses, as frontline patient care providers, are the foundation for patient safety and care quality. Promoting nurse empowerment, engagement, and interpersonal relationships at work is rudimental to achieve a healthy work environment and quality patient care. Healthier work environments lead to more satisfied nurses who will result in better job performance and higher quality of patient care, which will subsequently improve healthcare organizations' financial viability. Fostering a healthy work environment is a continuous effort. Keys words: Care quality, Nurse, Nursing leadership, Self-care, Work environments